Supply chain competition model with a NEV-sharing platform: Financing and risk attitude concerns. (October 2022) - Cai, Jianhu; Jia, Lishuang; Ping, Minyan
Highlights: Dig out key feature of NSP by introducing TSR services. Relate financial constraint and risk aversion together to describe NSP. Obtain SC members' preferences for MF strategy and MI strategy. Find SC members' preferences for asset-heavy mode and asset-light mode. Abstract: Currently, many platforms provide time-sharing rental (TSR) services to consumers by operating new energy vehicles (NEVs). We develop a two-echelon supply chain (SC) consisting of one NEV-sharing platform (NSP) and one original equipment manufacturer (OEM) under demand uncertainty. The NSP provides TSR services and operates under two operation modes: the asset-heavy mode and the asset-light mode. Under the asset-heavy mode, the NSP is risk averse and capital constrained, and seeks financing services from two SC finance strategies: OEM financing (MF) strategy and OEM investment (MI) strategy. Under the asset-light mode, the NSP is risk neutral and capital adequate. We derive and compare the SC members' optimal decisions under different SC finance strategies and different operation modes, then investigate SC members' participation motivations by comparing their benefits, the SC members' preferences for the SC finance strategies and the operation modes in different situations are obtained. Our results reveal that under the asset-heavy mode, there exists an interval of interest rate or an interval of supplementary investment where the SC members can benefit from the specific finance strategy compared with another finance strategy. This paper also shows that the SC members' preferences for different operation modes are influenced by the revenue-sharing ratio under the asset-light mode. Numerical examples are provided to validate our findings and to derive managerial implications.